Effect of surface cleaning methods on bond strength between canal sealer-contaminated dentin and composite resin - Gülşah Tonga; Fatih Uçar; Tunahan Döken; Ahmet Özlü (BMC Oral Health)
Abstract Background Sealer residues on dentin can affect bonding to restorative materials. This study aimed to evaluate the effect of different surface cleaning protocols on the cleaning efficiency and microtensile bond strength of composite resin to dentin contaminated with root canal sealer. Methods A total of 58 teeth were used in the study (36 for µTBS and 22 for SEM-EDX). Dentin surfaces were exposed and contaminated with an epoxy resin-based sealer (AH Plus) or a bioceramic-based sealer (T-endo Bioserra). Four cleaning methods were examined: dry cotton pellet, cotton pellet with 75% ethanol, surfactant-based cleaner (Katana™ Cleaner), and 37.5% orthophosphoric acid. Control samples had no sealer or cleaning method. Dentin surfaces were bonded with universal adhesive (Scotchbond Universal) and restored with resin composite (Filtek™ Z250). Specimens were divided into subgroups to compare bond strength before and after aging. Bond strength testing was performed using the microtensile bond strength (µTBS) testing. Two teeth from each group were used for SEM and EDX to evaluate cleaning efficiency, and zinc/zirconium percentages were measured to indicate the remaining filler. Results Bioserra contaminated groups exhibited smaller µTBS values than AH Plus contaminated groups. These values were significant in dry cotton pellet/immediate, ethanol/aged, and KatanaTM/ immediate groups (p˂0.05). Artificial aging decreased µTBS in all groups. This effect was significant in Bioserra/ethanol, AH Plus/Katana™, and Bioserra/phosphoric acid groups (p˂0.05). The lowest µTBS was observed in the dry cotton /Bioserra/aged group and the highest in the phosphoric acid/Bioserra/immediate group. Conclusions Dry and ethanol-impregnated cotton pellet methods are ineffective in removing sealers or increasing bond strength. Katana™ Cleaner and phosphoric acid cleaning effectively cleans and improves bond strength for epoxy and bioceramic sealers.